Stand productivity, carbon content, and soil nutrients in different stand ages of Acacia mangium in Sarawak, Malaysia - Lee, King Ling; Ong, Kian Huat; King, Patricia Jie Hung; Chubo, John Keen; Shan, Dennis An Su (Scientific and Technological Research Council of Turkey, 2015)
Land degradation and declining soil fertility challenge the productivity of forest plantations. Changes in soil properties could act as indicators for monitoring forest plantation management and productivity. This study highlights changes in soil properties and stand productivity over time (1, 3, and 5 years) in an Acacia mangium plantation in Bintulu, Sarawak, Malaysia. Soil pH, total N concentration, and available P were found to decline significantly with stand age. Significant differences were observed between soil organic C for different stand ages, with the youngest stand showing the highest C. The study showed that the current A. mangium plantation was able to store 74.9, 89.9, and 138.9 t C ha-1 in the 1-, 3-, and 5-year-old stands, respectively, and soil was the main contributor for the total C pools. All soil chemical attributes showed declining trends with stand age. These declines indicated that the present management practices are not sustainable and that management inputs are necessary.